Time-evolved SERS signatures of DEP-trapped Aβ and Zn2+Aβ peptides revealed by a sub-10 nm electrode nanogap - Vu, Katrin Ha Phuong (2021)
Alzheimer’s disease (AD) has become highly relevant in aging societies, yet the fundamental molecular basis for AD is still poorly understood. New tools to study the undergoing structural conformation changes of amyloid beta (Aβ) peptides, the pathogenic hallmark of AD, could play a crucial role in the understanding of the underlying mechanisms of misfolding and cytotoxicity of this peptide. It has been recently reported that Zn2+ interacts with Aβ and changes its aggregation pathway away from less harmful fibrillar forms to more toxic species. Here, we present a versatile platform based on a set of sub-10 nm nanogap electrodes for the manipulation and sensing of biomolecules in the physiological condition at a low copy number, where molecules are trapped via dielectrophoresis (DEP) across the nanogap, which also serves as a surface-enhanced Raman spectroscopy hotspot. In this study, we demonstrate that our electrode nanogap platform can be used to study the structural difference between Aβ40 and ZnAβ40 peptides at different aggregation stages in the physiologically relevant concentration and in solution phase. The Raman spectroscopic signatures of the DEP-captured neuropeptides prove the device to be attractive as a label-free bioanalytical tool.